Devaluation and professional teacher fulfillment: philosophy teachers' perceptions - Gabriel, Fábio Antonio; Pereira, Ana Lúcia (Universidade Estadual de Campinas, 2022)
The teaching career has been devalued, especially by neoliberal policies that tend to trivialize the teacher’s profession. Therefore, this paper aims to highlight the perceptions of Philosophy teachers regarding their performance in the profession. The subjects were 208 Philosophy professors from the state of Paraná, Brazil, who answered to a questionnaire. The methodology used for data analysis was the Textual Discourse Analysis (ATD), and for the categorization of responses the Atlas Ti software was used. The results indicate that the majority of subjects feel fulfilled, despite the devaluation, and the family needs to have a partnership in the teaching and learning processes.